Susceptibility profile of clinical and environmental isolates of Cryptococcus neoformans and Cryptococcus gattii in Uberaba, Minas Gerais, Brazil. (August 2013) - Andrade-Silva, Leonardo; Ferreira-Paim, Kennio; Mora, Delio Jose; Silva, Paulo Roberto Da; Andrade, Anderson Assunção; Araujo, Natalia Evelyn; Pedrosa, André Luiz; Silva-Vergara, Mario León
Abstract Cryptococcus neoformans and C. gattii are the etiologic agents of cryptococcosis, a life-threatening disease in both immunocompromised and immunocompetent hosts. Antifungal resistance has been evaluated using different methods, breakpoints, and sizes of test populations and it is an emerging as a significant issue worldwide. A total of 176 (95 clinical and 81 environmental) C. neoformans and eight clinical C. gattii isolates were evaluated to determine the minimal inhibitory concentration (MIC) according to the Clinical and Laboratory Standards Institute method. A total of 10.5% of the C. neoformans clinical isolates were resistant to amphotericin B (AMB), and 6.2% of the environmental isolates were resistant to fluconazole (FLZ). Environmental and clinical isolates presented epidemiologic cut-off values (ECVs) of 64 and 16 to FLZ and 1 and 2 to AMB, respectively. All of the C. gattii isolates showed high susceptibility to most drugs evaluated. Clinical isolates had lower susceptibility than environmental isolates to AMB and itraconazole whereas environmental isolates had lower susceptibility than the clinical isolates to FLZ, voriconazole, and ketoconazole. However, no difference was found in the susceptibility of the two species. The MICs and ECVs to antifungals can help to select the best therapeutic option for tracking epidemiological resistance among clinical and environmental isolates of Cryptococcus spp. around the world.